(untitled) (Journal of the College of Basic Education, 2022)
The aim of the current research is to find out the extent of benefiting from: "The use of plastic waste in handicrafts to develop creative thinking skills among students of the Department of Art Education."In order to achieve the sole objective of the research, the researcher put the following zero hypotheses:1- There are no statistically significant differences at the level of significance (0.05) in the ranks of total creative thinking skills among third-stage students between the pre and post applications.2- There are no statistically significant differences at the level of significance (0.05) in the ranks of the third-stage fluency skill between the pre and post applications.3- There are no statistically significant differences at the level of significance (0.05) in the ranks of flexibility skill among third-stage students between the pre and post applications.